2020
DOI: 10.30845/aijss.v9n4p3
|View full text |Cite
|
Sign up to set email alerts
|

The Determination of Academic Stress Levels by Gender and Year of Study. A Case of Kenyan University Students

Abstract: The main purpose of this study was to determine the influence of gender, type of university, year of study and age on the level of stress among university students in Kenya. The study was conducted among Bachelor of Education students in universities located in western Kenya. The sample was 410 students with an equivalent number of male and female students. The study adopted a quantitative research design. Academic Stress Level (ASL) questionnaire was the main instrument used in collecting data. Data was analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
1
1
2
Order By: Relevance
“…Research results confirm that gender (β = -0.088, p=0.65>0.05 and year of study (β = 0.085, p=0.162>0.05) do not affect students' academic stress. These findings quite similar to previous research results of Hạnh (2018) [14] , Gao et al (2020) [12] , Laigong & Shikuku (2020) [19] , Ekka (2022) [9] .…”
Section: Resultssupporting
confidence: 92%
“…Research results confirm that gender (β = -0.088, p=0.65>0.05 and year of study (β = 0.085, p=0.162>0.05) do not affect students' academic stress. These findings quite similar to previous research results of Hạnh (2018) [14] , Gao et al (2020) [12] , Laigong & Shikuku (2020) [19] , Ekka (2022) [9] .…”
Section: Resultssupporting
confidence: 92%
“…Our findings show that male students had a significantly higher mean score in perceived academic stressors than their female counterparts, indicating that male students might be more stressed than their female counterparts. Over the years, researchers have tried to understand how students differ in their perception of stressors based on gender Calaguas, 2011;Chemutai, Mulambula, 2020). The finding of this study that male students have a significantly higher mean score in perceived sources of academic stress contradicts the findings of Calaguas (2011) and Chemutai and Mulambula (2020).…”
Section: Discussioncontrasting
confidence: 70%
“…Over the years, researchers have tried to understand how students differ in their perception of stressors based on gender Calaguas, 2011;Chemutai, Mulambula, 2020). The finding of this study that male students have a significantly higher mean score in perceived sources of academic stress contradicts the findings of Calaguas (2011) and Chemutai and Mulambula (2020). They found that female students were more prone to stressors.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation